2022
DOI: 10.1108/ijem-05-2022-0173
|View full text |Cite
|
Sign up to set email alerts
|

Insights from online education in the Egyptian higher education

Abstract: PurposeThe introduction of technology in education has been a strategic objective at both the governmental and educational institutional levels long before Covid-19. However, the acceleration to e-learning caused by the pandemic disrupted the traditional classroom environment overnight forcing the entire sector at all levels, school, undergraduate and postgraduate, to shift to online learning. Regardless of readiness, the action was taken, and online instruction was implemented, improved, adjusted and enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Continual education among individuals in the workforce has become an inevitable factor in the modern economic climate (Park and Kim, 2023). Research shows that due to the dynamic business environment and advanced technology that led to credentials of workers being out-of-date, growing appreciation of the importance of lifelong learning exists (Kumar, 2022), increasing demand for higher education programs, such as executive education, among people outside the typical 18–24 age group (Salman and Soliman, 2023). Like so, Freyn et al .…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Continual education among individuals in the workforce has become an inevitable factor in the modern economic climate (Park and Kim, 2023). Research shows that due to the dynamic business environment and advanced technology that led to credentials of workers being out-of-date, growing appreciation of the importance of lifelong learning exists (Kumar, 2022), increasing demand for higher education programs, such as executive education, among people outside the typical 18–24 age group (Salman and Soliman, 2023). Like so, Freyn et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Understanding student’s satisfaction has initiated a line of research both in developing and developed nations (as shown in Table 1), exploring various factors influencing its development in both online and offline learning approaches. Student’s satisfaction has been examined in various social context, such as Turkey (Turan and Gurol, 2020; Ma et al ., 2021), United States (Shin and Hickey, 2020), Egypt (Mohamed et al ., 2020; El-Sayad et al ., 2021; Salman and Soliman, 2023), Korea (Park and Kim, 2023), Spain (Atilgan et al ., 2021), Malaysia (Mohammed et al ., 2022), Poland (Cicha et al ., 2021), Singapore (Wan and Chapman, 2022) and India (Kumar, 2022). However, few studies reviewed the factors that lead to satisfaction in blended learning, linking face-to-face and distance learning frameworks jointly to upturn learning advantages (Graham et al ., 2019), especially when it comes to developing nations (Salman and Soliman, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations